2019
DOI: 10.1002/ajpa.23849
|View full text |Cite
|
Sign up to set email alerts
|

Age at death estimation by cementochronology: Too precise to be true or too precise to be accurate?

Abstract: Objectives: Cementochronology based on annual deposition of acellular cementum is acknowledged for its superior performance for estimating age-at-death but is also disregarded because of its suspicious effectiveness. This article aims to provide a standardized framework for the validation of the technique and to define and test cementochronology's performance and limitations. Materials and methods:To determine the boundaries of the cementum aging technique, we applied a certified protocol on a sample of 200 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 81 publications
1
36
0
Order By: Relevance
“…To date, incremental layers may only be imaged to a satisfying extent at synchrotron radiation facilities 37 or by means of conventional optical microscopy of thin sections. 32,34,36 A laboratorybased μCT was suggested by Mani-Caplazi et al 3 based on physically sliced samples and a close source-sample position. In the current study, we showed that advanced laboratory instrumentation generates great potential for facilitating high-resolution incremental layer imaging in a nondestructive manner.…”
Section: Human Tooth Cementum-requirement For Non-destructive Imaging...mentioning
confidence: 99%
“…To date, incremental layers may only be imaged to a satisfying extent at synchrotron radiation facilities 37 or by means of conventional optical microscopy of thin sections. 32,34,36 A laboratorybased μCT was suggested by Mani-Caplazi et al 3 based on physically sliced samples and a close source-sample position. In the current study, we showed that advanced laboratory instrumentation generates great potential for facilitating high-resolution incremental layer imaging in a nondestructive manner.…”
Section: Human Tooth Cementum-requirement For Non-destructive Imaging...mentioning
confidence: 99%
“…Nonetheless, cervical acellular extrinsic fiber cementum provides the steadiest growth rate conserving layer thickness [20,21,24]. Unfortunately, counting of layers is error-prone and observer-dependent, leading most commonly to an underestimation of age, despite of high-resolution imaging methods [28,29]. Further investigation is therefore desired and suggested in archeological samples with corresponding life history [24,29].…”
Section: Tooth Root Cementuma Lifelong Growing Mineralized Tissuementioning
confidence: 99%
“…Until now, incremental layers may only be imaged to satisfying extent at synchrotron radiation facilities [29] or by means of conventional optical microscopy of thin sections [24,26,28]. A laboratory-based µCT was suggested by G. Mani-Caplazi [2] based on physically sliced samples and a close source-sample position.…”
Section: Human Tooth Cementumrequirement For Non-destructive Imaging ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation of the final age is done by adding the age of the root formation to the mean number of counted cementum layers, since forming of cementum begins after the root development. Different studies report different protocols and errors for the described method for age determination (Gauthier & Schutkowski, 2013;Bertrand et al, 2019;Penezic´ et al, 2019) so there is a need for the standardization of the procedure, that can be used within the anthropological, archeological, forensic and histological context.…”
Section: Introductionmentioning
confidence: 99%